Study protocol for a randomised controlled trial with clinical, neurophysiological, laboratory and radiological outcome for surgical versus non-surgical treatment for lumbar spinal stenosis: the Uppsala Spinal Stenosis Trial (UppSten) - Karl Michaëlsson; Konstantinos Pazarlis; Anna Punga; Nikos Schizas; Bengt Sandén; Peter Försth (BMJ Open)
Introduction Symptomatic lumbar spinal stenosis is the most common indication for spinal surgery. However, more than one-third of the patients undergoing surgery for lumbar stenosis report dissatisfaction with the results. On the other hand, conservative treatment has shown positive results in some cases. This trial will compare the outcomes of surgical versus non-surgical treatment for lumbar stenosis. The study includes a multidimensional follow-up, aiming to study the association between outcome and other studied parameters, mainly electromyography and nerve conduction. Moreover, it may contribute to a better understanding of the pathophysiology of lumbar stenosis and to the development of future pharmacological treatments.Methods and analysis UppSten is a single-centre randomised controlled trial in which 150 patients with symptomatic lumbar spinal stenosis will be randomised into one of two treatment arms. The patients in the surgical arm will undergo laminectomy; the patients in the non-surgical arm will be given a structured physical training programme. The primary outcome of the study will be the Oswestry Disability Index. Secondary outcomes will include motor amplitude and degree of denervation activity obtained by means of nerve conduction studies and electromyography. Patient-reported outcome measures will be also used as secondary outcomes. Blood sample analysis and the investigation of potential inflammation markers are the additional secondary outcome parameters. Laboratory evaluation will include blood sample collection before the treatment initiation and after 6 months. Flavum ligament biopsies will be performed in the surgical group. Finally, tertiary outcomes will include neurophysiological measures, the objective walking ability and radiological evaluation.Ethics and dissemination The study is approved by the Local Ethics Committee (Dnr 2017–506), the Hospital’s Clinical Trials Committee (2018–0001) and the National Biobank Council and Uppsala Biobank (BbA-827-2018-025). The results will be presented in peer-reviewed journals and at international conferences.Trial registration number NCT03495661